"This Group Is Vital": Adult Peers in Community for Support and Learning. Issue 2 (May 2018) - Cherrstrom, Catherine A.; Zarestky, Jill; Deer, Shannon
Adult learners often experience uncertainty, isolation, and, in graduate school, angst about meeting program requirements. Therefore, graduate students created and facilitated a seminar series and preliminary examination study group. The experience, however, transcended seminars and study meetings to build relevant and meaningful community. The purpose of this qualitative study was to examine adult peers in community for support and learning. Major findings included participants built community for support and learning, using programming as foundation for building a community of practice (CoP), with peer mentoring playing a major role. The findings also feature participant voices and share programming ideas for adult learners and educators.